2016
DOI: 10.1099/jmmcr.0.005047
|View full text |Cite
|
Sign up to set email alerts
|

Non-traumatic keratitis due to Colletotrichum truncatum

Abstract: Introduction:The fungal genus Colletotrichum is an uncommon cause of human infections. It has been implicated in cutaneous phaeohyphomycosis, artritis and keratitis secondary to traumatic implantation.Case presentation:We report two cases of keratitis due Colletotrichum truncatum in middle-aged, immunocompetent persons without history of trauma. The aetiological agents were identified based on DNA sequencing. Azoles and echinocandins showed high minimal inhibitory concentrations while amphotericin B was ≤ 0.25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Among the known species of Colletotrichum , C. dematium is the most reported pathogen for keratitis, followed by C. gloeosporioides and C. truncatum. In our study, all seven isolates belonged to two species complexes: C. truncatum and C. gloeosporioides and no C. dematium . C. dematium has been synonymised with many species, especially C. truncatum , but now they are found phylogenetically distinct and belongs to their own clades .…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…Among the known species of Colletotrichum , C. dematium is the most reported pathogen for keratitis, followed by C. gloeosporioides and C. truncatum. In our study, all seven isolates belonged to two species complexes: C. truncatum and C. gloeosporioides and no C. dematium . C. dematium has been synonymised with many species, especially C. truncatum , but now they are found phylogenetically distinct and belongs to their own clades .…”
Section: Discussionmentioning
confidence: 57%
“…It used to be an infrequent cause—accounting for 1.85%‐3.33%—of fungal keratitis diagnosed by smear and cultures . Current knowledge of Colletotrichum keratitis is based on sporadic case reports and a few small case series from various countries, including India, the United States, Japan, Spain, Canada, and Cuba . Previous studies reported that the ratio of Colletotrichum spp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations